2019
DOI: 10.17305/bjbms.2019.4176
|View full text |Cite
|
Sign up to set email alerts
|

Age- and gender-independent association of glutathione S-transferase null polymorphisms with chronic myeloid leukemia

Abstract: The glutathione S-transferase (GST) genes encode enzymes that mediate the detoxification of xenobiotics by catalyzing the conjugation of glutathione (GSH) to xenobiotic substrates. The aim of the current study is to investigate the association between GSTT1 and GSTM1 polymorphisms and chronic myeloid leukemia (CML) among Sudanese patients. Patients with CML (n = 115) were recruited to the study from the Radiation and Isotope Centre Khartoum (RICK)-Sudan. Healthy individuals (n = 104) were included as controls.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
(47 reference statements)
2
4
2
Order By: Relevance
“…Therefore, the GSTT1 genotype may be a protective factor for CML, whilst the null genotype showed an association with the development of CML. The above findings were in agreement with a recent study conducted in Sudan (Muddathir et al, 2019). Many studies have focused on the relationship between GSTT1 polymorphism and the risk of CML in diverse ethnic groups (Bajpai et al, 2007;Al-Achkar et al, 2014;Kassogue et al, 2015).…”
Section: Genotypessupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, the GSTT1 genotype may be a protective factor for CML, whilst the null genotype showed an association with the development of CML. The above findings were in agreement with a recent study conducted in Sudan (Muddathir et al, 2019). Many studies have focused on the relationship between GSTT1 polymorphism and the risk of CML in diverse ethnic groups (Bajpai et al, 2007;Al-Achkar et al, 2014;Kassogue et al, 2015).…”
Section: Genotypessupporting
confidence: 93%
“…Interestingly, no association between GSTM1 null genotype and the risk of CML was found here: (OR =0.975, 95% CI: 0.578-1.584; p-value = 0.863). However, Muddathir and his co-workers found that GSTM1 null genotype was associated with increased risk of CML among Sudanese (Muddathir et al, 2019). This is not unexpected because Sudan is multiethnic with an admixture of Arab and African lineages which may be associated with differences in genetic makeup.…”
Section: Genotypesmentioning
confidence: 99%
“…Therefore, identification of these genes in our antiretroviral-prescribed patients could facilitate the determination of higher-risk groups. The frequency of the double deletion found in our population 11.2% was lower than those reported in Ivory Coast 14.3% [24], Ghana 16.66% [26], Morocco 15.5% [27], Egypt 16.25% [28], Tunisia 18% [28] and Sudan 32.9% [29], but higher than that seen in Algeria 7.31% [30] and Namibia 3% [31]. The distribution of the mutant allele G in GSTP1 gene observed in our population 49.76% was statistically comparable to that reported in the Gambian population 53.6%, (p = 0.2).…”
Section: Discussioncontrasting
confidence: 69%
“…The results of the study by Hamed et al in 2019 showed different results from ours, namely there was an insignificant difference in the mean number of leukocytes in the TET2 gene polymorphism rs34402524 in the LGK population (p = 0.07). Different results were also reported by Muddathir et al in 2019 which showed that there was no difference in the mean number of leukocytes in the GSTT1 and GSTM1 polymorphisms (p = 0.254 and p = 0.797) [8].…”
Section: Discussionmentioning
confidence: 58%